2019
DOI: 10.26710/reads.v5i2.599
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Effectiveness of Technical and Vocational Education in Pakistan

Abstract: An investigation and validation of effectiveness of technical and vocational education at secondary level for poverty alleviation is need of the day. Four sub-components such as locale, age, education and socio economic status have been considered important in determining the effectiveness of technical & vocational education at secondary level for poverty alleviation. Out of 815 pass outs in Matric technology and vocational education during 2013, 2014 and 2015, the parents of 494 were selected through prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Based on the results, it is concluded that a significantly strong effect of T&VE is found on Poverty Reduction. These results have supported the results from (Pervez, 2014;Siddiqui et al, 2019;Zhang, 2021), who all have concluded that Technical & Vocational Education plays a significant and positive role in poverty reduction.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Based on the results, it is concluded that a significantly strong effect of T&VE is found on Poverty Reduction. These results have supported the results from (Pervez, 2014;Siddiqui et al, 2019;Zhang, 2021), who all have concluded that Technical & Vocational Education plays a significant and positive role in poverty reduction.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…Pakistan is also working hard to eradicate poverty using several measures. The provision of technical and vocational education is one of the measures that have been taken to eradicate poverty (Siddiqui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some students showed less interest than others and had no motivation to learn new skills or face new challenges (Usoro & Etuk, 2016). C u r r e n t l y, r e s e a r c h o n T V E T programmes in Pakistan has been mainly anchored on demographic differences, facilities, funding, curriculum, and enrolment (Azeem et al, 2022;Chamadia & Shahid, 2018;Siddiqui et al, 2019). Furthermore, there is insufficient literature to provide information regarding the cognitive factors influencing school students' interest in TVET programmes in Pakistan.…”
Section: Technical and Vocational Education Andmentioning
confidence: 99%
“…They underscored the need for investing in developing workforce skills to raise productivity and competitiveness required to attain economic growth and poverty reduction. Siddiqui et al (2019) investigate the effectiveness of VET programs for poverty alleviation in Pakistan. They conducted a descriptive study to find the parents' perception toward poverty alleviation through vocational training programs.…”
Section: Hypothesis Developmentmentioning
confidence: 99%